DINASTI FATHIMIYAH MASA KEMAJUAN DAN KONTRIBUSI DINASTI FATIMIYAH TERHADAP PERADABAN ISLAM - SOHEH, MOH; SUBHAN, MOH (AHSANA MEDIA: Jurnal Pemikiran, Pendidikan dan Penelitian Ke-Islaman, 2020)
In the history of Islam, following the reign of the Rasyidin Rashidun, was succeeded by rulers who formed power with a system of family power or dynasty. Starting from the Muawiyah powers that formed the Umayyad dynasty, the system of democracy was transformed into a hereditary monarchi (Hereditary kingdom). The Muawiyah was acquired by violence and diplomacy, not with the most elections or votes. The succession of hereditary instantly leadership begins when the Muawiyah obliges all people to declare true to his son, Yazid, who later succeeded him. Muawiyah intends to model the Monarchi in Persia and the Byzantines. Muawiyah miming The term caliph, but he gave a new interpretation of the words to glorify the position. The dynasties in power after the Rashidun Rashidun were the Umayyad dynasty, the Abbasid dynasty, the Umyyaah dynasty in Andalusia, the Syafawiyah dynasty, the Ottoman dynasty in Turkey, the Mongol Empire of Islam in India, and many other dynasties ruling on several Part of the Islamic world. In addition to these dynasties, there were also several other dynasties that also embraced the important role in the development of civilization in the Islamic world including the Fathimiyah dynasty which has a great contribution to the civilization of Islamic world